2020
DOI: 10.1002/ejp.1584
|View full text |Cite
|
Sign up to set email alerts
|

The N2pc component as a neural index of early attention allocation among adults with chronic musculoskeletal pain

Abstract: Theories of pain-related attention biases (ABs) have posited that people are predisposed to focus upon pain because prioritizing attention towards potential threats enhances survival (Eccleston & Crombez, 1999). Unfortunately, when ongoing pain is an attentional priority over extended intervals, healthy behaviours may be compromised, impairment may be compounded and pain chronicity may become entrenched (Vlaeyen & Linton, 2000). In sum, pain-related ABs are hypothesized to increase risk for the development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Therefore, it may be helpful for future studies use eye movement indices that quantify overall attention over the entire duration of each trial. Indexes from event-related potentials such as N2 posterior contralateral amplitudes provide a neural marker of early attention allocation that has potential utility as an alternative measure of pain-related orienting biases (Wang et al, 2020).…”
Section: Eye Movement Analyses Eye Movements and Pain 29mentioning
confidence: 99%
“…Therefore, it may be helpful for future studies use eye movement indices that quantify overall attention over the entire duration of each trial. Indexes from event-related potentials such as N2 posterior contralateral amplitudes provide a neural marker of early attention allocation that has potential utility as an alternative measure of pain-related orienting biases (Wang et al, 2020).…”
Section: Eye Movement Analyses Eye Movements and Pain 29mentioning
confidence: 99%
“…To assess N2pc amplitudes elicited by angry versus happy facial expressions with greater precision, great grand average N2pc waveforms were generated from eight samples that assessed angry facial expressions (Diao et al., 2017; Feldmann‐Wüstefeld et al., 2011; Grimshaw et al., 2014; Liu et al., 2017; Osinsky et al., 2014; Reutter et al., 2019; Yao et al., 2013, 2014) and eight samples that examined happy facial expressions (Diao et al., 2017; Feldmann‐Wüstefeld et al., 2011; Grimshaw et al., 2014; Liu et al., 2017; Wang et al., 2020; Yao et al., 2013, 2014). Figure 3 illustrates GGA results.…”
Section: Resultsmentioning
confidence: 99%
“… In studies that reported separate N2pc results for angry and happy facial expressions, effect sizes were pooled for each sample and averaged for inclusion in the meta‐analysis. However, in calculating the moderating effects of facial expression, anger‐induced and happy‐induced N2pc amplitudes were calculated separately for each sample. For one included mood state induction study (Liu et al., 2017), N2pc amplitude results were included only from neutral control conditions and were excluded from conditions featuring affectively valenced mood state inductions (e.g., after watching violent video). In studies that included distinct distressed groups (e.g., high trait socially anxious and chronic pain) (Holmes et al., 2013; Wang et al., 2020; Wieser et al., 2018) as well as healthy subgroups, N2pc amplitude effect sizes were calculated separately for each subgroup. In the moderator analysis for sample type, N2pc effect sizes were calculated separately for nondistressed/healthy versus distressed/less healthy subgroups (e.g., chronic pain and high social anxious). When results were reported for separate N2pc components (e.g., early vs. late N2pc (Feldmann‐Wüstefeld et al., 2011; Holmes et al., 2009; Holmes et al., 2013) or face image pair durations (e.g., 500 ms vs. 1,000 ms) from the same sample (Grimshaw et al., 2014; Osinsky et al., 2014; Yao et al., 2013), effect sizes were pooled and averaged to provide an overall effect size for the sample. However, in calculating moderating effects of time window, early (<250 ms) versus late (>250 ms) N2pc effects were calculated separately for each sample. In studies that featured interventions (Osinsky et al., 2014; Reutter et al., 2019), only pretreatment N2pc results were included for analysis to maintain consistency with designs of other included studies. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations